Role of Railway Transportation in the Spread of the Coronavirus: Evidence From Wuhan-Beijing Railway Corridor - Liu, Rucheng; Li, Dan; Kaewunruen, Sakdirat (Frontiers in Built Environment, 2020)
The last few months have marked a notable surge in COVID-19. The disease has infected 10 million people around the world and has gained attention in the field of research. Allegedly originating in China, the virus has spread to nearly every country. The current study aims to analyze the potential spread of the coronavirus through rail transport by considering the case of the Wuhan-Beijing railway corridor in China. It has been found that approximately 43,000 people travel daily through this railway line, which indicates a high chance for this railway line to spread the virus. This study adopts a quantitative methodology to analyze the spread of the disease due to a large number of people traveling on the Wuhan-Beijing railway line. The findings of this study establish that the railway line leaving Wuhan carries approximately 43,000 people daily. The more people travel, the higher the chances are for the spread of the disease through this railway line. In line with that, the study has also analyzed the effectiveness of control measures such as lockdown, the use of masks, sanitization, and social distancing for railway authorities as well as passengers. This study concludes by proposing new practical recommendations for further controlling the spread of the disease in Wuhan.